PENGARUH INFLASI TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - R.Titin Sumarni, Indra Masrin (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2016)
Higher inflation will cause the real consumption rate of society to goods and servicefrom a company become lower, so it will affect the rate of company’s profit, which alsoaffect the Stock Price in the company. In this research, the formulation of the problem iswhether inflation can affect the price of stock in the Manufacture Company listed inIndonesian Capital Market in 2008-2014 and the purpose of this research is to understandthe effect of inflation to the price of stocks in Manufacture Company listedin IndonesianCapital Market in 2008-2014.This research uses secondary data from Indonesian Capital Market with thepopulation is a group of Manufacture Company listed in Indonesian Capital Market innumber of 158 companies. The sampling method used in this research is PurpossiveSampling, so the sample will be 73 Manufacture Company listed in Indonesian CapitalMarket in 2008-2014.The result showed the negative relation between inflation and the price of stock, butstatistically, it is not significant because thitung - 0,148 < ttabel 2,015 and α 0,05 sig 0,888.Keyword: Stock Price, Inflationand Manufacture Company.